Unfolding the Political Capacities of Design - Fernando Domínguez Rubio; Uriel Fogué (Diseña, 2018)
The aim of this article is to discuss the political capacities of design. The usual way of exploring the relation between design and politics has focused on design’s ability to enfold the political, that is, to inscribe political codes into things, places, and bodies, operating at a sub-political level. An exploration is proposed of an alternative way of thinking about how design can become political matter: the propositional capacity to unfold the political, that is, to extend, interrogate and speculate about the types of things, places and bodies that constitute the cosmos of the political, operating at a level that is cosmopolitical.